Peer Group Optimization in Developing Religious Culture of High School Students - Zainal Abidin; Jaudi Jaudi; Imaduddin Imaduddin; Mukhaemin Mukhaemin (Nazhruna: Jurnal Pendidikan Islam, 2022)
The background of this research is the decline of religious culture among young people and students alike, then the influence of peer groups (Peer Group) was very strong in shaping the character of students for the need to optimize Peer groups in developing the religious culture of SMA Negeri 1 Pacet Mojokerto students. The focus of research in this study is 1) Optimization of Peer Group in developing the religious culture of SMA Negeri 1 Pacet Mojokerto students, 2) The constraints of optimizing Peer Group in developing the religious culture of students of SMA Negeri 1 Pacet Mojokerto. The method used is the descriptive qualitative method. Data collection techniques using direct observation, interviews, and documentation. The data analysis stage uses the Milles and Huberman method which is done through data reduction, data presentation, verification, and conclusions. Checking the validity of the data using triangulation techniques. The subjects of this study are the Principal, Islamic Religious Education Teachers, and Students as additional subjects, while the object is the Peer Group and religious culture. The results of this study note that the optimization of the Peer Group at SMA Negeri 1 Pacet Mojokerto in developing religious culture went smoothly. The constraints in optimizing Peer Group in SMA Negeri 1 Pacet Mojokerto in developing students' religious culture in the form of internal, external, and endogenous factors.